Cyberbullying and online harms preventions and interventions from community to campus - Cowie, Helen; Myers, Carrie-Anne (Routledge, Taylor & Francis Group, 2023)
"Cyberbullying and Online Harms identifies online harms and their impact on young people, from communities to campuses, exploring current and future interventions to reduce and prevent online harassment and aggression. This is essential reading for researchers, academics, undergraduates and postgraduates in sociology, psychology, criminology, media and communication studies, as well as practitioners and policymakers in psychology, education, sociology, criminology, psychiatry, counselling and psychotherapy, and anyone concerned with the issue of bullying, cyberbullying and online harms among young people in higher education"